Relation between half‐cell and fuel cell activity and stability of FeNC catalysts for the oxygen reduction reaction. Issue 5 (8th October 2022) - Scharf, Janik; Kübler, Markus; Gridin, Vladislav; Wallace, William David Zacharias; Ni, Lingmei; Paul, Stephen Daniel; Kramm, Ulrike Ingrid
Abstract: FeNC catalysts are promising substitutes of platinum‐type catalysts for the oxygen reduction reaction (ORR). While previous research disclosed that high pyrolysis temperatures are required to achieve good stability, it was identified that a trade‐off needs to be made regarding the active site density. The central question is, if a good stability can also be reached at milder pyrolysis conditions but longer duration retaining more active sites, while enabling the defect‐rich carbon to heal during a long residence time? To address this, a variation of pyrolysis temperatures and durations is used in FeNC fabrication. Carbon morphology and iron species are characterized by Raman spectroscopy and Mössbauer spectroscopy, respectively. Fuel cell (FC) activity and stability data are acquired. The results are compared to ORR activity and selectivity data from rotating ring disc electrode experiments and resulting durability in accelerated stress tests mimicking the load cycle and start‐up and shut‐down cycle conditions. It is discussed how pyrolysis temperature and duration affect FC activity and stability. But, more important, the results connect the pyrolysis conditions to the required accelerated stress test protocol combination to enable a prediction of the catalyst stability in fuel cells. Abstract : The best protocol of accelerated stress tests to mimic the degradation of FeNC in fuel cells depends on the preparation conditions. At mild preparation conditions both, carbon oxidation and active site disintegration overlay, but active site destruction contribute to a major extent. At high pyrolysis conditions carbon oxidation dominates, and an overall much better stability is obtained.